2020
DOI: 10.3389/fphar.2020.549117
|View full text |Cite
|
Sign up to set email alerts
|

Positive RT-PCR Test Results in 420 Patients Recovered From COVID-19 in Wuhan: An Observational Study

Abstract: Objective: During the follow-up of patients recovered from coronavirus disease 2019 (COVID-19) in the quarantine and observation period, some of the cured patients showed positive results again. The recurrent positive RT-PCR test results drew widespread concern. We observed a certain number of cured COVID-19 patients with positive RT-PCR test results and try to analyze the factors that caused the phenomenon. Methods: We conducted an observational study in COVID-19 patients discharged from 6 rehabilitation stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…Excluded studies and the reason are shown in appendix pp 107–110. Of the 117 eligible studies, there were 66 case reports [ 5 , 16 – 80 ], 42 case series [ 6 , 81 – 121 ], 3 cohort studies [ [122] , [123] , [124] ], 3 cross-sectional studies [ 125 127 ] and 3 case-control studies [ 128 – 130 ]. One hundred studies were from China, 7 from Italy, 3 from Korea, 2 from France, 5 each from Iran, Brunei Darussalam, Switzerland, America and Portugal.…”
Section: Resultsmentioning
confidence: 99%
“…Excluded studies and the reason are shown in appendix pp 107–110. Of the 117 eligible studies, there were 66 case reports [ 5 , 16 – 80 ], 42 case series [ 6 , 81 – 121 ], 3 cohort studies [ [122] , [123] , [124] ], 3 cross-sectional studies [ 125 127 ] and 3 case-control studies [ 128 – 130 ]. One hundred studies were from China, 7 from Italy, 3 from Korea, 2 from France, 5 each from Iran, Brunei Darussalam, Switzerland, America and Portugal.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, the loss of smell and taste for weeks cannot be considered in defining the recovered cases [38] . However, the reverse transcription polymerase chain reaction (RT-PCR) test conducted on the four patients who met the criteria for hospital discharge were tested positive after 10 days of the hospital discharge [ 39 , 40 ]. In a study, [8] Fotios presented a brief insight on the importance of recovered cases, They reported the recovered cases are increasing exponentially as the number of days in the pandemic increase.…”
Section: Resultsmentioning
confidence: 99%
“…7 Administrative Office, The Third People's Hospital of Shenzhen, Shenzhen, China. 8 Department of Hepatology III, The Third People's Hospital of Shenzhen, Shenzhen, China. 9 Department of Internal Medicine, Fankou Branch of Ezhou Central Hospital, Ezhou, China.…”
Section: Resultsmentioning
confidence: 99%
“…Yang’s study involving 93 re-positive patients showed that 72% (67/93) of the re-positive patients were clinically classified as asymptomatic infection, and the median of viral RNA level in recurrent-positive patients was 3.2 log10 copies/ml (ranged from 1.8 to 5.7) [ 5 ]. Another study involving 420 patients showed that 45.2% (190/420) of re-positive patients were asymptomatic [ 8 ]. As the condition of asymptomatic infection was hidden, the identification of risk factors of recurrent positive was one of the key points of COVID-19 prevention and control [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation